Kajian kritis tentang histori problematika kesetaraan gender dalam perspektif pendidikan Islam - Darwis, Adnan; Supraha, Wido; Tamam, Abas Mansur (TAWAZUN: Jurnal Pendidikan Islam, 2024)
Gender equality in the history of human civilization, especially in the pre-Islamic context, has been a discourse that continues to be criticized until now, especially by feminists. This gender problem is often associated with the story of the creation of Adam and Eve, which although it has been criticized, is still used as a basis for understanding gender equality. This research aims to critically examine the history of gender equality problems in the perspective of Islamic education. This research uses qualitative, descriptive, and library research methods. The results show that the philosophy of Islamic education, which is based on the Quran and hadith, has brought significant improvements to the condition of women since pre-Islamic times until now. This conclusion contradicts the Western concept of gender equality that often distances humans from their nature. This research emphasizes the importance of the Islamic educational perspective in promoting equality of dignity and opportunities for activities and achievements of women properly and correctly, which places the glory of women as it should be, and according to the dignity and dignity of women in the sight of Allah Ta'ala. Abstrak Kesetaraan gender dalam sejarah peradaban manusia, terutama dalam konteks pra-Islam, telah menjadi diskursus yang terus dikritisi hingga kini, khususnya oleh kaum feminis. Problematika gender ini sering dikaitkan dengan kisah penciptaan Adam dan Hawa, yang meskipun telah dikritisi, masih dijadikan dasar dalam memahami kesetaraan gender. Penelitian ini bertujuan untuk mengkaji secara kritis histori problematika kesetaraan gender dalam perspektif pendidikan Islam. Penelitian ini menggunakan metode kualitatif, deskriptif, dan library research. Hasil penelitian menunjukkan bahwa filosofi pendidikan Islam, yang berlandaskan pada Quran dan hadits, telah membawa perbaikan signifikan bagi kondisi perempuan sejak masa pra-Islam hingga kini. Kesimpulan ini bertentangan dengan konsep kesetaraan gender dari Barat yang sering menjauhkan manusia dari fitrahnya. Penelitian ini menegaskan pentingnya perspektif pendidikan Islam dalam mengusung kesetaraan harkat dan kesempatan beraktivitas dan berprestasi para kaum perempuan secara baik dan benar, yang menempatkan kemuliaan perempuan sebagaimana mestinya, dan sesuai harkat dan martabat kewanitaannya di hadapan Allah Ta’ala.